Childhood blindness from surge of advanced stage retinopathy of prematurity in premature infants during the COVID-19 pandemic: a case series - Yulia, Dian Estu; Soeharto, Diajeng Ayesha (Universa Medicina, 2023)
Background Retinopathy of prematurity (ROP) is a proliferative disease of the ocular retinal vasculature in premature infants, being a leading cause of preventable childhood blindness. The COVID-19 pandemic serves as an additional barrier to access to care and referral, potentially leading to more cases of advanced stage ROP. Although surgery can be done, ROP at this stage is highly associated with poor functional outcome irrespective of surgery. This case series aims to report advanced stage (stage 5) ROP in premature infants during the COVID-19 pandemic. MethodsA retrospective case series of medical records of paediatric patients with ROP was performed at Cipto Mangunkusumo National Referral Hospital between March 1, 2020 and December 31, 2021. This case series included new patients that presented to our clinic from March 2020 to December 2021 with stage 5 ROP. ResultsA total of 19 eyes of 10 patients with stage 5 ROP were included in this study. Mean chronologic age at presentation to our referral centre was 7.0 4.0 months. Upon presentation, all had stage 5 ROP with negative blink reflex to light, and none of the eyes in this cohort underwent surgical intervention. Mean gestational age was 30.3 3.2 weeks and mean birth weight was 1,276.7 366.4 g. ConclusionThere was an observable surge of stage 5 ROP at our referral centre with irreversible blindness. This highlights the need for proper ROP screening in all hospitals in Indonesia to prevent delay in detection and care of advanced stage ROP.